Intranasal Ketamine as an Adjunct to Fentanyl for the Prehospital Treatment of Acute Traumatic Pain: Design and Rationale of a Randomized Controlled Trial. (19th June 2021) - McMullan, Jason; Droege, Christopher; Strilka, Richard; Hart, Kimberly; Lindsell, Christopher
Abstract: Objective : Acute pain management is fundamental in prehospital trauma care. Early pain control may decrease the risk of developing post-traumatic stress disorder (PTSD) and chronic pain. Fentanyl and ketamine are frequently used off-label, but there is a paucity of comparative data to guide decision-making about treatment of prehospital severe, acute pain. This trial will determine whether the addition of single dose of intranasal ketamine to fentanyl is more effective for the treatment of acute traumatic pain than administration of fentanyl alone. Methods : This two-part study consists of prehospital and 90-day follow-up components (NCT02866071). The prehospital trial is a blinded, randomized, controlled trial of adult men (age 18-65 years) rating pain ≥7/10 after an acute traumatic injury of any type. Women will be excluded due to inability to confirm pregnancy status and unknown fetal risk. Paramedics will screen patients receiving standard of care fentanyl and, after obtaining standard informed consent, administer 50 mg intranasal ketamine or matching volume saline as placebo. Upon emergency department (ED) arrival, research associates will serially assess pain, concomitant treatments, and adverse side effects. Enrolled subjects will be approached for consent to participate in the 90-day follow-up study to determine rates of PTSD and chronic pain development. The primary outcome of the prehospital study is reduction in pain on the Verbal Numerical Rating Scale between baseline and 30-minutes after study drug administration. The proportion achieving a reduction of ≥2-points will be compared between study arms using a Chi-square test. Secondary outcomes of the prehospital trial include reduction in reported pain at the time of ED arrival and at 30 minutes intervals for up to three hours of ED care, the incidence of adverse events, and additional opiate requirements prior to ED arrival and within the first three hours of ED care. The outcomes in the follow-up study are satisfaction with life and development of PTSD or chronic pain at 90 days after injury. An intention-to-treat approach will be used. Conclusion : These studies will test the hypotheses that ketamine plus fentanyl, when compared to fentanyl alone, effectively manages pain, decreases opiate requirements, and decreases PTSD at 90 days.